Social Capital and Entrepreneurial Competencies: a study among Women Micro-Entrepreneurs in Malaysia. - Abdullah Al- Mamun; Rajennd Muniady; P. Yukthamarani Permarupan; Noor Raihani Zainol; Noorshella Che Nawi; C. A. Malarvizhi (2015)
Women entrepreneurship as one of the key contributors of economic development through a rapid development process reduces poverty, unemployment, and inequalities, and improves the overall well being of children. Social capital is the most under-rated influential factor, which may have a strong influence on entrepreneurial competencies and enterprise performance. This study aims to examine the effect of social capital (i.e., structural, cognitive, and relational) on entrepreneurial competencies (i.e., conceptual, commitment, and organizing) among women micro-entrepreneurs in Peninsular Malaysia. This study employs a cross-sectional approach and quantitative data are collected through structured interviews. It was found that social capital has a significant positive effect on entrepreneurial competencies. Development policies and programs in Malaysia should therefore focus on building social capital among micro-entrepreneurs to foster the national development process that reduces poverty, unemployment rate, and inequalities.